Język szkolnej edukacji w perspektywie glottodydaktycznej – zarys problematyki - Seretny, Anna (Postscriptum Polonistyczne, 2020)
The number of migrant children at Polish schools is increasing. They should use the Polish language not only to communicate at school and beyond, but also to understand the world. In order to achieve this goal certain actions must be taken because the development of the necessary communicative and cognitive skills does not occur spontaneously. The article presents the specificity of the term language of education, distinguishing it from language of everyday communication, and proves its importance for children’s educational achievements. The article author also proves the necessity of distinguishing between shaping the linguistic communicative skills and cognitive language proficiency.